Aplikasi Ekstrak Daun Binahong (Anredera cordifilia) terhadap Kondisi Fisiologis Saluran Pencernaan dan Organ Viceral pada Broiler - N. Irwani; A. A. Candra (Politeknik Negeri Lampung, 2020)
Binahong leaves contain flavonoids and saponins which can be used as antioxidants, so that they can affect the body's metabolic process. Binahong leaves (Anredera Cordifolia) contain flavonoid compounds which are useful as antioxidants, can also increase appetite so that the growth and production of chickens are as expected. Giving saponins can increase the permeability of cell walls in the intestine, as well as increase the absorption of nutrients. Researchers are interested in conducting further studies on the physiological conditions of the digestive tract and visceral organs. The place of research is the Animal Laboratory of Lampung State Polytechnic and the Chicken Cage at Lampung State Polytechnic. The treatments in this study were administration of binahong leaf extract which was applied in drinking water with a dose of 0; 25; 50; and 75 mg / kg BW. The experimental design used a 4x5 RAL, each plot containing 10 docs. The data from the research results were analyzed for variety, if the results were real, then continued with the BNJ at the 5% level. Based on observations and analysis of research data, it can be concluded that binahong leaf extract in drinking water with a dose of up to 100 mg / kg affects the live weight and visceral organs (weight of the liver, ventriculus, and small intestine) of broiler chickens, but the best dose has not been found.